Help Your Child to Succeed : The Essential Guide for Parents - Lucas, Bill, 1956- and Smith, Alistair (London Network Continuum, 2009)
Shows how families can enjoy learning together, for the home and its immediate environment offer wonderful opportunities for discovery, exploration, play, education and learning. This book contains activities, games, tips and suggestions for dealing with everyday concerns, such as helping with homework and things to do in the school holidays.
Include Color Illustrations
Previous edition: 2002.
Keywords: Readiness for school -- Success in children -- Child rearing